KOMUNIKASI INTERPERSONAL FRONTLINER DALAM MELAYANI DAN MEMBERIKAN INFORMASI KEPADA PELANGGAN PT.PLN (PERSERO) RAYON PANAM PEKANBARU - Hennike Ramadhani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Frontliner interpersonal communication is very important in the service and information to customers of PT. PLN (Persero) Rayon Panam. The presence, these interpersonal communication, Frontliner and customers can find out how to establish a good relationship with each other. The purpose of this study was to determine how effective interpersonal communication Frontliner serve and provide information to customers, as well as to identify factors that affect interpersonal communication Frontliner in serving and providing information to customers of PT. PLN (Persero) Pekanbaru Panam Rayon.The research was conducted at PT. PLN (Persero) Pekanbaru Panam Rayon, which is located at Jalan HR. Soebrantas Pekanbaru. This research using qualitative research methods. Informants in this study is 15 people. Where 6 people frontliner using purposive technique and 5 customers, using accidental. Techniques of data collection is done through observation, interviews and documentation. Data analysis techniques include data reduction data presentation, conclusion and verification.The results showed that the effectiveness of interpersonal communication components frontline in serving and providing information to customers must be effective, because the frontliner should be able to be a communicator has high credibility and has the appeal so as to convey the message or information directly or indirectly (media), and can understood by the communicant (customers) so get the effect of what is being implemented in the frontline to serve and provide information to customers. Factors that affect interpersonal communication frontliner in serving and providing information to customers including the trust factor, factor supportiveness and openness factors. The trust factor where customers lack confidence with what is provided by the front liners, and factors supportiveness which is not supportive of the PLN in serving and providing information to customers. While the openness factor, frontliner has been open to the problems experienced by PT PLN.Keywords : Interpersonal Communication, frontliner, customers